Chromatographic beads, their production and use

By preparing and functionalizing small, rigid and impermeable agarose beads, the problem that existing HPLC stationary phases are difficult to achieve high resolution and low nonspecific adsorption when analyzing biomolecules is solved, and efficient and safe biomolecule analysis and preparation applications are achieved.

CN112292203BActive Publication Date: 2025-05-02CYTIVA BIOPROCESS R&D AB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980043553.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-29
Filing Date
2019-06-25
Publication Date
2025-05-02
Estimated Expiration
2039-06-25

AI Technical Summary

Technical Problem

Existing HPLC stationary phases are difficult to achieve rapid separation of high resolution and low nonspecific adsorption when analyzing biomolecules, and the solvents used have environmental, health and safety issues.

Method used

Small, rigid and impermeable agarose beads are used as stationary phases, and solid agarose beads with high rigidity and high surface area are prepared through technical means such as crosslinking and polymer antenna grafting, and functionalized on their surface to increase interaction sites.

Benefits of technology

It realizes rapid analytical applications under high pressure and large-scale preparative applications under low pressure, with high resolution, low non-specific adsorption and high pH tolerance, avoiding the risk of using harmful solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112292203B_ABST
    Figure CN112292203B_ABST
Patent Text Reader

Abstract

The present invention relates to chromatography beads, their production and use. More specifically, the present invention relates to small, rigid and impermeable agarose beads suitable, for example, as stationary phase in high performance liquid chromatography (HPLC) for the analysis of biomolecules, such as peptides and proteins; and methods for producing said beads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chromatography beads, their production and use. More specifically, the present invention relates to small, rigid and impermeable agarose beads, which are primarily suitable as stationary phases, e.g. in high performance liquid chromatography (HPLC), for the analysis of biomolecules, such as peptides and proteins; and methods for producing said beads. Background Art

[0002] HPLC (High Performance Liquid Chromatography) is a liquid chromatography method, which is essential for the research, manufacture and diagnosis of chemical and biochemical compounds. Biomolecules (such as peptides, proteins and their potential variants) are often characterized and analyzed in high pressure chromatography systems due to the speed and resolution obtained. Two types of columns are mainly used for conventional analysis. They are packed columns or monolithic columns. Packed columns contain particulate stationary phases that are most often in the shape of spherical beads, which are closely packed with each other and the column bed height range is 3-30 cm. Due to its rigidity, commercially available stationary phases for HPLC columns are usually based on silica or synthetic organic resins such as polystyrene. Using beads of smaller diameter in shorter columns is a very effective way to achieve high-efficiency separation at a fast rate, but it also means a relatively high back pressure. Therefore, only very rigid stationary phase materials are used. The most commonly used technique is reversed phase chromatography.

[0003] Packed columns Currently available HPLC stationary phases are based on 1.7-10 µm beaded silica or synthetic polymers, where the small diameter of the beads results in increased chromatographic efficiency.

[0004] The main challenge in analytical protein separations is to obtain fast separations with high resolution and low nonspecific adsorption. The beads in the packed columns are either porous or nonporous, with their own advantages and disadvantages. Silica and synthetic nonporous particles have the advantage of short diffusion paths and binding only on the bead surface, which means faster mass transfer. Porous beads offer a larger surface area, which means more sites for interaction with the analyte and higher binding capacity.

[0005] Other types of stationary phases for HPLC have been described. In US 5135650, Hjertén et al. describe the method that porous agarose beads are converted into substantially impermeable protein beads by shrinking beads or filling holes. By carrying out sequential treatment with different organic solvents (such as dioxane and chloroform) and in conjunction with cross-linking, the shrinkage of Hjertén method is carried out. Filling is carried out by adding polymerizable substances such as glycidol, which allows part to be attached to internal holes and bead surfaces. Final beads are described as having enough reduced porosity to prevent molecular weight from being 3 kDa or higher protein infiltration, and the column filled with these beads has shown that the highest pressure that can withstand 40 bars. The major disadvantage of the shrinkage method is the use of solvents, such as dioxane, which is usually avoided due to environment, health and safety reasons. Summary of the invention

[0006] The present invention provides small, rigid and impermeable agarose beads suitable as stationary phase in high performance liquid chromatography (HPLC) for the analysis of biomolecules, such as peptides and proteins, and also for preparative use on a larger scale.

[0007] The present invention provides solid agarose beads with rigidity to exclude compounds as small as 100 g / mol, ie, substantially excluding even the simplest dipeptides.

[0008] In a first aspect, the present invention relates to solid agarose beads, wherein the agarose beads are rigid and impermeable to compounds with a molecular weight as low as 3000 g / mol, preferably 100 g / mol.

[0009] Preferably, the beads have a diameter of 1-25 μm, preferably 1-15 μm for HPLC and preferably 15-25 μm for preparative applications.

[0010] Solid agarose beads according to the invention withstand pressures in excess of 100 bar, preferably pressures ≥ 300 bar, for rapid analytical applications at high pressure and larger scale preparative applications at low pressure. Small beads - high pressure. Large beads - low pressure.

[0011] Preferably, solid agarose beads are provided with tentacles / grafted polymers to increase surface area and enable functionalization.

[0012] The antennae or bead surfaces may be provided with ligands, such as cationic ligands, anionic ligands, affinity (Protein A, IMAC) ligands, hydrophobic interaction ligands, or combinations thereof.

[0013] In one embodiment of the invention, the solid agarose beads have a diameter of 1-15 μm and are packed in an HPLC column. One or more HPLC columns can be connected to the HPLC system. When more than one column is provided, the beads of the column preferably have different functionalities (different ligands are connected).

[0014] In a second aspect, the present invention relates to a method for producing the above-mentioned solid agarose beads, comprising the steps of: providing agarose beads having a diameter of 5-50 μm in a solution having an agarose concentration of 8-20% (w / w); heating the solution to a constant temperature of about 45-99° C. and emulsifying the agarose beads in the solution; crosslinking the beads at least once; activating the beads by, for example, allylation; and optionally grafting polymer tentacles on the beads to attach ligands. Alternatively, the ligands may be attached to the surface of the beads. Other examples of activation are epoxy activation, NHS or CNBr activation.

[0015] Preferably, ligands such as affinity ligands, ion exchange ligands and hydrophobic interaction ligands are provided on the polymer tentacles.

[0016] In one embodiment, magnetic particles, such as magnetite particles, are added to the solution prior to the emulsification step.

[0017] In a third aspect, the invention relates to the use of the above solid agarose beads for the analysis of biomolecules, such as proteins and peptides, for example in terms of analyte concentration, charged or hydrophobic variants and characterization. Molecules as small as 100 g / mol are excluded from the beads.

[0018] In one embodiment, the beads have a diameter of 1-15 μm and are used in high performance liquid chromatography (HPLC) applications.

[0019] In another embodiment, the beads are 15-25 μm in diameter and are used in preparative and / or large-scale applications, such as purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Shown is a graph showing the average HPLC system pressure at different flow rates on a connected 4.6 mm (id) x 10 cm PEEK column packed with non-porous agarose beads from Example 1.

[0021] Figure 2 shows a comparative chromatogram of the separation of aprotinin. Figure 2A Shown is the separation of aprotinin from Example 2 on non-porous agarose beads packed in a 4.6 mm (id) x 10 cm PEEK column using a 10 minute linear gradient of 0-500 mM sodium chloride at 1.66 ml / min. Figure 2BShown is the separation of aprotinin on a prior art Mini S column, 3.2 mm (id) x 3 cm, using a 10 min linear gradient of 0-500 mM sodium chloride, 0.80 ml / min. mAU - Units at 214 nm.

[0022] Figure 3 shows Figure 3A : The non-porous agarose beads from Example 2 were in a PEEK column and Figure 3B : Comparative chromatograms of peak resolution of mAb separations on prior art MonoS columns. Separation of charged variants of a monoclonal antibody on an ion exchange column using an increasing pH gradient. 46 µg of monoclonal antibody loaded on each column. mAU - units at 280 nm. DETAILED DESCRIPTION OF THE INVENTION

[0024] The inventors assume that agarose beads can be made hard enough to withstand high pressure by collapsing the natural pore structure, and small enough to compete with currently available HPLC resins in terms of resolution and efficiency. Similarly, the mass transfer of analytes in columns filled with these non-porous beads will also be improved, resulting in sharper peaks. In order to increase the interaction between the analyte and the ligand fixed on the beads, surface grafting is performed after collapse to increase the available surface area. The production method is based on a first agarose emulsification step, followed by a second pore collapse step, combined with cross-linking of the beads before polymer-tentacle grafting. The beads can then be functionalized with the same type of ligand used for conventional porous agarose-based resins, such as to achieve affinity chromatography, ion exchange chromatography and hydrophobic interaction chromatography. Compared with silica-based HPLC beads, the advantage is that pH tolerance is improved, especially at alkaline pH. Compared with non-polar synthetic polymer HPLC beads, agarose-based beads are still naturally hydrophilic. This is advantageous in the technology of wishing to minimize the undesirable hydrophobic interaction between the analyte and the gel resin.

[0025] The inventors have shown that agarose beads with an average diameter of 3-6 μm can be produced and columns packed with these beads are HPLC compatible and can be operated at pressures of at least 300 bar. Unexpectedly, the beads exclude compounds as small as 100 g / mol, essentially excluding even the simplest dipeptides. This enables efficient mass transfer and sharp, narrow peaks for relevant biomolecules of all sizes. Furthermore, the signal-to-noise ratio will benefit from sharper peaks.

[0026] In one embodiment of the invention, the beads of the invention have been functionalized with weak cation exchange ligands and functional testing has been performed using samples with peptides and proteins ranging from 6 kDa to 160 kDa with superior resolution and analysis speed compared to prior art techniques.

[0027] The present invention describes methods for producing solid or non-porous agarose beads grafted with polymer tentacles for analytical HPLC or high resolution preparative applications, which offer a unique combination of benefits compared to previously described stationary phases: alkaline stability, hydrophilic resins and rapid mass transfer, with increased surface area.

[0028] Some general and exemplary principles for producing solid agarose beads according to the present invention are described below:

[0029] 1. Emulsification

[0030] Agarose beads with a diameter of 5-50 μm and a concentration of 8-20% (w / w) agarose in water are used as a starting point for producing the small agarose beads of the present invention. Any suitable emulsification method can be used, for example using an organic continuous phase, preferably toluene, with or without a membrane device with a suitable pore size or by stirring. Methods for emulsifying agarose beads are described in US6602990 and US7396467.

[0031] 2. Solidification and collapse

[0032] The high temperature step before cross-linking is used to solidify the agarose pore structure in the bead form and make the beads non-porous. The pre-step collapses the agarose pore structure and makes it denser before cross-linking. In this step, the temperature is usually set at 45-99°C.

[0033] 3. Cross-linking

[0034] The pre-step is followed by a cross-linking step using a cross-linking agent such as epichlorohydrin in the presence of sodium hydroxide. Methods for cross-linking agarose are described in US6602990 and US7396467.

[0035] 4. Hole filling

[0036] Filling of the remaining pore volume is carried out by several additional steps of extensive crosslinking using, for example, epichlorohydrin in the presence of sodium hydroxide.

[0037] The remaining pore volume can also be filled by coupling allyl glycidyl ether (AGE) in the presence of sodium hydroxide, followed by deactivation and hydrolysis. The process of activation with allyl glycidyl ether and deactivation with bromine is described in EP 1 357 988 A1.

[0038] 5. Functionalization (optional)

[0039] Functionalization is carried out by grafting the polymer onto the activated matrix by polymerization. Activation can be carried out by coupling with allyl glycidyl ether (AGE). The method for this step is described in EP2841177B1.

[0040]

[0041] Coupling of allyl glycidyl ether, which can be used to activate or fill residual pore volume

[0042] The monomers can be grafted onto the activated beads by mixing one, two or several different monomers with a suspension of particles in water and a free radical initiator. The grafting onto the activated beads is carried out by free radical polymerization. The method of grafting monomers onto activated beads is also described in EP2841177B1.

[0043] Experimental Section

[0044] Example 1: Preparation of non-porous agarose beads

[0045] emulsification

[0046] Solid beads are prepared from beaded agarose by the following procedure. 209 g agarose is suspended in 1800 ml water and heated to 95°C to dissolve agarose (10% (w / w)), and the temperature is then reduced to 70°C. The agarose solution is added to an organic phase containing 2250 ml of toluene, a surfactant (tenside) and a cellulose emulsifier at 60°C to form a coarse emulsion. The emulsion is pumped (pressurized) through a hydrophobic SPG membrane for repeated passages to obtain a narrow particle size distribution. The collected emulsion is cooled to 22-20°C and washed with ethanol to remove toluene and emulsifier. The emulsified agarose beads are finally washed with water to remove ethanol before cross-linking.

[0047] Two parallel procedures were performed to generate different emulsified agarose bead sizes, 5 μm and 10 μm, respectively.

[0048] Solidification and collapse

[0049] Weigh the emulsified agarose gel resin and set the concentration of the slurry in water to 75% (419 ml gel volume, 559 ml slurry). The gel is transferred to a reactor under stirring and placed in a water bath. The gel resin is heated to 35 ° C, and 218 g of Na2SO4 is added to the mixture. The mixture is placed at 35 ° C for 70 minutes. The mixture is then heated to the set shrinkage temperature, and the evaluation temperature is 87 ° C. The reaction is placed at the set temperature for 60 minutes. After the temperature is reduced to 47.5 (± 1 ° C), 5.6 ml of 25M NaOH solution is added to the reaction, and then 0.5 g of NaBH4 is added to the reaction.

[0050] Cross-linking

[0051] The cross-linking agent (epichlorohydrin) and 25 M NaOH solution were added using a dosing device for 5 hours, and the total amount of 25 M NaOH and epichlorohydrin added was 61.5 ml volume, respectively. The reaction was placed at 47.5°C under stirring for 19±2 hours (including the 5 hours of adding the cross-linking agent). The gel resin was then washed on a glass filter with distilled water (6x2 gel volumes).

[0052] Weigh the cross-linked gel resin, and the concentration of the slurry in water is set to 70%. Under agitation, the gel is transferred to a round-bottomed flask. Add 4.32g NaAc and dissolve it for 15 minutes. Then add bromide 0.345ml to the slurries, and after the mixture turns yellow, the reaction is placed for 15 minutes. After 15 minutes, the residual bromide is destroyed with 0.7 gram of sodium formate until the slurry turns white. Sodium formate is placed to dissolve for 15 minutes, then the temperature is raised to 40 ℃ and 48.1g Na2SO4 is added and the reaction is placed for 60 minutes. 13.75ml of 25M NaOH solution is added to the mixture, and the reaction is placed at 40 ℃ for 16-20 hours under agitation. The gel resin is then washed with distilled water (6x2 gel volume) on a glass filter.

[0053] Filling of pores by repeated cross-linking

[0054] The hydrolyzed gel resin was weighed and the slurry concentration was set to 75% gel and the rest was distilled water. The gel resin was transferred to a reactor with a water bath and stirring. The gel was heated to 33°C and 42.6g Na2SO4 was added to the mixture. The mixture was placed at 33°C for 70 minutes. Afterwards, the temperature was raised to 47.5 (±1°C) and the mixture was placed for 60 minutes while stirring. 1.1ml 25M NaOH solution was added to the reaction. Crosslinking agent (epichlorohydrin) and NaOH were added with dosimats for 5h, and the total amount of NaOH and epichlorohydrin added was 12 ml volume each. The reaction was placed at 47.5°C for 19 (±2 hours) under stirring. The gel was then washed with distilled water (6x2 gel volumes) on a glass filter.

[0055] Filling of holes by allylation

[0056] The gel slurry was weighed, added to a glass filter, and washed with 50% NaOH solution (2x1 gel volume). The gel was drained and added to the reactor with an equal amount of 25M NaOH (e.g. 100g of drained gel plus 100ml 25M NaOH). Stirring was started at 200rpm. Afterwards, NaBH4 (1g for 100g of gel) was added. The gel slurry was heated to 50°C, and then allyl glycidyl ether (AGE) (100g of gel plus 200ml AGE) was added. Stirring was increased to 300rpm. The reaction was left overnight (16-20 hours) at 50°C. The next day, the gel slurry was added to a glass filter and washed with distilled water (3x2 gel volumes), ethanol (5x2 gel volumes), and distilled water (5x2 gel volumes).

[0057] result

[0058] Determination of size

[0059] The resulting beads were analyzed by size measurement using a laser diffraction particle size analyzer. After this procedure, the average diameter of the shrunken agarose beads was approximately 3 and 5 µm when starting from initially 5 and 10 µm emulsified agarose beads, respectively.

[0060] Determination of porosity

[0061] A 4.6 mm (inner diameter) x 10 cm PEEK column was filled with 5 μm non-porous beads from Example 1 at a constant pressure of 100 bar for 15 minutes. AV To determine the value, the voids must be known, which is measured by the retention volume of a high molecular weight compound (e.g. Blue Dextran 2000). Porosity is determined by measuring the volume of the injected compound, Blue Dextran 2000 (2x10 6 The retention volume of Blue Dextran 2000 is 0.78 ml, and the K values ​​of potassium nitrate (Ve 0.78 ml) and acetone (0.79 ml) were obtained using a geometric volume of 1.66 ml as Vt. AV The values ​​are 0 and 0.01 respectively. The internal volume of a column is usually measured by subtracting the void volume from the elution volume of small molecules, in this case this gives 0-0.01 ml for all but very small compounds, i.e. a non-porous chromatographic stationary phase.

[0062] Example 2: Preparation of non-porous agarose beads with cation exchange ligands

[0063] This example illustrates the preparation of a cation exchanger by derivatizing the non-porous agarose beads of Example 1, starting from 5 μm non-porous agarose beads.

[0064] The drained gel resin is poured into a three-ended round flask. Add the ionic monomer VSA, the neutral monomer VP and water, see the scheme below. Adjust the pH to pH 7-8 with acetic acid and NaOH. Then add the initiator 2,2'-azobis(2-methyl-propionamidine) dihydrochloride (ADBA) and lower a tube with a continuous nitrogen flow into the dispersion. The flask is then lowered into a water or glycerol bath and the reaction is left at 48-50°C for 16-20 hours with stirring. The gel resin is then washed with distilled water (6x2 gel volumes) on a glass filter. The gel resin is titrated to measure the ionic capacity after the reaction.

[0065]

[0066] Polymerization of monomers onto activated beads using vinyl pyrrolidone (VP) and vinyl sulfonate (VSA)

[0067] Example 3: Pressure and flow rate performance of non-porous agarose beads

[0068] This example demonstrates the pressure-flow rate performance of the non-porous agarose beads of the present invention.

[0069] At a constant pressure of 100 bar, a 4.6 mm (inner diameter) × 10 cm PEEK column was filled with non-porous beads of 5 μm average diameter from Example 1 for 15 minutes. Then, the PEEK column was connected to a high-pressure HPLC system (Agilent 1260 Infinity II) using a PEEK hand-tightening joint. Water was pumped to the column starting with a flow rate of 0.5 ml / min (181 cm / h linear flow rate) and gradually increased to 3.9 ml / min (1408 cm / h). The average system pressure at different flow rates was recorded. Figure 1 The relationship between flow rate and system pressure was shown to be linear over the entire range, indicating that the column can be operated at flow rates up to at least 4 ml / min.

[0070] Example 4: Chromatographic separation (comparative example)

[0071] 4A

[0072] This example compares the peak efficiency of aprotinin (6.5 kDa) separated in a gradient from low to high salt on a Mini S column (GE Healthcare) and a PEEK column packed with non-porous beads of Example 2. In addition, a chromatogram comparison of a monoclonal antibody (160 kDa) separated with an increasing pH gradient from pH 6-9 is shown between the Mono S column and the Example PEEK column.

[0073] A packed column containing beads of Example 2 having an average diameter of 5 μm and an ionic capacity of 37 μmol / ml was prepared as in Example 3. The column was equilibrated with 20 mM sodium phosphate, pH 6.5. Aprotinin (1 mg) was dissolved in 1 ml of equilibration buffer and 20 μl (equivalent to 20 μg) was injected onto the column. Bound aprotinin was eluted with a linear gradient of 0-500 mM NaCl at a linear flow rate of 600 cm / h over 10 min. A Mini S column, 3.2 mm (id) x 3 cm, was run in comparison to the same method and linear flow rate but with 5 μg of aprotinin injected. The peak efficiency, expressed as the width at half peak height, was 5.5 s for the column packed with non-porous agarose beads compared to 17.5 s for the Mini S column (0.1 s and 0.2 s, respectively). Figure 2A and B).

[0074] 4B

[0075] A PEEK column filled with non-porous agarose beads from Example 2 was equilibrated with 10 mM sodium citrate, 10 mM sodium phosphate, 10 mM Tris (pH 5.3). The monoclonal antibody (recombinantly produced in CHO cells and purified on a protein A affinity column) was diluted from 28 g / L to 2 g / L in 10 mM sodium phosphate (pH 6.5), and 23 µl (equivalent to 46 µg of antibody) was injected onto the column. The bound antibody was eluted with a linear gradient from the equilibration buffer at pH 5.3 to the elution buffer at pH 8.7 at 600 cm / h over 10 minutes. A Mono S column, 5 mm (inner diameter) x 5 cm, was run compared to the same method but with a reduced linear flow rate and increased gradient time (300 cm / h for 20 minutes). A comparison of the resolution between the main peak (highest peak) and the acidic and basic variants before and after the main peak, respectively, can be seen in Figure 3. The PEEK column filled with non-porous beads showed improved performance at twice the speed.

Claims

1. A method for producing solid agarose beads which are rigid and impermeable to compounds having a molecular weight of 100 g / mol, the method comprising the following steps: providing agarose beads having a diameter of 5-50 μm in a solution having an agarose concentration of 8-20% (w / w); emulsifying the agarose beads in the solution; applying a high temperature step to solidify the agarose beads and collapse the agarose pore structure; cross-linking the beads at least once after emulsification; activating to shrink and fill the remaining pores in the agarose beads; and optionally adding a ligand to the beads.

2. The method of claim 1, wherein the activation is performed by allylation of the beads.

3. The method of claim 1, wherein the ligand is provided on polymer tentacles grafted onto the beads.

4. The method of claim 3, wherein the ligand is selected from the group consisting of affinity ligands, ion exchange ligands and hydrophobic interaction ligands.

5. The method according to claim 1 or 3, wherein magnetic particles are added to the solution before emulsification.

Citation Information

Patent Citations

  • A method for producing liquid chromatography matrices

    EP1357988A1

  • Separation method and separation matrix

    EP2841177B1

  • Process for the production of a porous cross-linked polysaccharide gel and its use as a gel filtration media and in chromatography

    US6602990B1

  • Method of preparing a chromatography matrix

    US7396467B2

  • Chromatography stationary phase material for high performance liquid chromatography

    US5135650A